Dermoscopic pattern of the topical steroid damaged face: A cross-sectional, observational study at a tertiary referral center in south India - Pappala Mamatha; Sruthi Kareddy; Haarika Sadhu (Our Dermatology Online, 2023)
Background: Unsupervised overuse of topical corticosteroids (TCs) is highly common in dermatological practice, leading to steroid abuse known as topical steroid damaged/dependent face (TSDF). Dermoscopy aids in the early detection of TSDF. Aims: The aim of this study was to evaluate the clinical and dermoscopic findings in patients with TSDF. Materials and Methods: The study was conducted on eighty patients presenting with clinical features suggestive of TSDF. Detailed history taking, clinical examination, and dermoscopic evaluation with a DermLite dermoscope were performed. Results: Out of the eighty patients included in the study, 64 (80%) were females and 16 (20%) were males. The most common age group affected was 18-30 years (52; 65%). Sixty-six were literate. Melasma was a common underlying condition for which a steroid was used by the patients (44; 55%). Betamethasone (34; 47.5%) was the most commonly used, followed by clobetasol (18; 22.5%). Relatives and friends were the common sources of recommendation (46; 57.5%). Most of the patients applied these for one year. Redness was the predominant presenting complaint, seen in sixty patients (75%). The common clinical findings were erythema (75%), hyperpigmentation (44; 55%), and hypertrichosis (50; 62.5%). The common findings observed on dermoscopy were telangiectasia (90%), red, diffuse areas (75%), brown globules (55%), and hypertrichosis (62.5%). In telangiectasia, the linear (60%), polygonal (30%), Y-shaped (25%), and serpentine (15%) types were seen. The other findings observed were white, structureless areas (37.5%), Demodex tails (25%), scaling (15%), pustules (10%), comedones (20%), and the breaking of the pseudo-reticular network (22.5%). Limitations: The limitation of this study was the lack of histopathological correlation. Conclusion: Dermoscopy aids in the early diagnosis of TSDF.